2021
DOI: 10.3329/bjmm.v15i2.57817
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Dengue Virus Serotypes in Dhaka City: From 2017 to 2021

Abstract: This is a retrospective observational study aimed to search the alteration of circulating dengue virus (DENV) serotypes in Dhaka City for five consecutive years (2017-2021) along with disease outcome. Methods: Routine dengue NS1 or PCR positive dengue samples from patients who visited Evercare Hospital Dhaka (ex. Apollo Hospitals Dhaka) were selected for serotype determination by serotype specific real time reverse transcriptase PCR (RT-PCR). Results: In 2017, predominant serotype was DENV-2 (91.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…However, in the years 2013–2016, DENV-1 and DENV-2 were the predominant serotypes in Bangladesh [ 47 ]. In 2017, DENV-2 was the predominant serotype (91.3%) in Dhaka City [ 48 ]. A recent study phylogenetically analyzed samples collected during the 2018 outbreak in Bangladesh and found cocirculation of serotypes 2 (54%) and 3 (46%) [ 49 ].…”
Section: Epidemiology Of Denv Infection and Correlation Of Serotypes ...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the years 2013–2016, DENV-1 and DENV-2 were the predominant serotypes in Bangladesh [ 47 ]. In 2017, DENV-2 was the predominant serotype (91.3%) in Dhaka City [ 48 ]. A recent study phylogenetically analyzed samples collected during the 2018 outbreak in Bangladesh and found cocirculation of serotypes 2 (54%) and 3 (46%) [ 49 ].…”
Section: Epidemiology Of Denv Infection and Correlation Of Serotypes ...mentioning
confidence: 99%
“…A recent study phylogenetically analyzed samples collected during the 2018 outbreak in Bangladesh and found cocirculation of serotypes 2 (54%) and 3 (46%) [ 49 ]. In 2018, among 127 cases, DENV-2 was reported as the predominant serotype (40.95%), followed by DENV-3 (33.07%) and DENV-1 (25.98%) [ 48 ]. During the 2019 and 2021 epidemics, DENV-3 was the predominant serotype [ 48 , 50 ].…”
Section: Epidemiology Of Denv Infection and Correlation Of Serotypes ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, DENV3 was the burgeoning serotype and there was no evidence of DENV2. More severe cases were observed in the 2019 outbreak of DENV3 [ 25 ]. It is possible that the weaker serotype-specific cross-reactivity between the re-emerged DENV3 and pre-existing major serotype DENV2 in 2013–2018 increased the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the introduction of new serotypes or genotypes can lead to outbreaks of severe dengue. We previously reported that the dominant serotype shifted from DENV2 in 2017 and 2018 to DENV3 from 2019 until August 2022, when the only prevalent serotype was DENV3 (100%) and there was no evidence of other serotypes [ 25 ]. In the present study, we conducted a phylogenetic analysis of the envelope protein region of DENVs to determine the viral genotypes and evolutionary relationships among past and present isolates [ 26 ].…”
Section: Introductionmentioning
confidence: 99%